2020
DOI: 10.5114/aoms.2019.86616
|View full text |Cite
|
Sign up to set email alerts
|

RIVAroxaban TWICE daily for lysis of thrombus in the left atrial appendage in patients with non-valvular atrial fibrillation: the RIVA-TWICE study

Abstract: Introduction: Rivaroxaban is a direct factor Xa inhibitor used once a day for prevention of thrombotic events in patients with atrial fibrillation (AF). However, in a small proportion of subjects thrombus in the left atrial appendage (LAA) is present despite this treatment. The aim of this study was assess the efficacy of increased dose of rivaroxaban (15 mg twice daily) treatment for lysis of thrombus in the LAA. Material and methods: In the RIVA-TWICE prospective, open label study, with non-blinded patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Little is known, however, about what kind of action should be undertaken if patient is diagnosed with thrombus in LAA despite apparently correct chronic OAC treatment [23]. Published data is scarce and limited mainly to small case series or case reports [9,[24][25][26]. In a survey conducted by the European Heart Rhythm Association (EHRA), responders reported over a dozen of potential options when dealing with OAC-resistant thrombus [8].…”
Section: Introductionmentioning
confidence: 99%
“…Little is known, however, about what kind of action should be undertaken if patient is diagnosed with thrombus in LAA despite apparently correct chronic OAC treatment [23]. Published data is scarce and limited mainly to small case series or case reports [9,[24][25][26]. In a survey conducted by the European Heart Rhythm Association (EHRA), responders reported over a dozen of potential options when dealing with OAC-resistant thrombus [8].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the CLOT-AF registry was to provide retrospective thrombus-related patient outcome data after standard-of-care anticoagulant therapy in patients with AFL or nonvalvular AF who had documented LAT/LAAT on TEE [36]. In contrast, the RIVA-TWICE study showed that the increased dose of rivaroxaban (15 mg twice daily in patients with AF and LAAT despite rivaroxaban 20 mg once a day therapy) was associated with LAAT resolution in 46.7% of participants [37]. Unfortunately, the RE-LATED_AFNET7 trial on the efficacy of dabigatran in LAA thrombus resolution has not been published due to its premature termination [38].…”
Section: Discussionmentioning
confidence: 99%
“…AF seems to be an underestimated factor. Patients with AF have more comorbidities and have a higher risk of complications [4,18,19].…”
Section: Discussionmentioning
confidence: 99%